Assessing the risk of intussusception and rotavirus vaccine safety in Canada. Issue 3 (4th March 2017) - Hawken, Steven; Ducharme, Robin; Rosella, Laura C.; Benchimol, Eric I.; Langley, Joanne M.; Wilson, Kumanan; Crowcroft, Natasha S.; Halperin, Scott A.; Desai, Shalina; Naus, Monika; Sanford, Carolyn J.; Mahmud, Salah M.; et al.
ABSTRACT: Background: Intussusception has been identified as a rare adverse event following rotavirus immunization. We sought to determine the incidence of intussusception among infants in Canada both before and after introduction of rotavirus immunization programs.Methods: We used Canadian Institute for Health Information (CIHI) Discharge Abstract Database (DAD) to identify infants under 1 y of age who were admitted to a Canadian hospital, which the exception of Quebec, which does not submit data to CIHI, with a diagnosis of intussusception (ICD-10 code K56.1, and ICD-9 code 560) between January 1st, 2003 and December 31, 2013. We compared rates of intussusception hospitalization before and after rotavirus vaccine program introduction. Rates were adjusted for calendar year, age (in months), sex and region using Poisson regression models. Denominator data for infants under 1 year, stratified by age in months, were obtained from Statistics Canada.Results: Annual intussusception hospitalization rates ranged from 20-30 per 100, 000 infants over the study period, with no evidence of a trend over time. Intussusception hospitalization rates were highest in infants 4 to <8 months and lowest in those under 2 months or between 10 and <12 months. Males had higher rates than females both overall and within each age group. The rate of intussusception hospitalization after rotavirus vaccine program introduction was 22.4 (95% CI: 18.3, 27.4) compared to 23.4 (95% CI: 21.5, 25.4) per 100, 000 before program introduction.Conclusions: We have described baseline intussusception hospitalization rates for infants in Canada and have found no evidence of a change in rate after implementation of routine rotavirus immunization programs.